Pendampingan Gerakan Peduli Budaya Dengan Menyanyikan Lagu Daerah di SDN Ledokombo 02 - Alivia Rosita Wahyuni; Diny Fajariani Kusumaningtyas; Ichtiar Syahru Ramadhan; Marsella Putri Permatasari; Astri Widyaruli Anggraeni (Lembaga Pengembangan Kinerja Dosen, 2024)
This research is motivated by the lack of cultural awareness among elementary school students. Assistance in singing regional songs aims to preserve local culture through an educational approach among students. Students are taught to sing regional songs as part of cultural preservation. Through this activity, it is hoped that students will be able to appreciate and love local culture, so that they can foster a sense of nationality and love for their homeland. Apart from that, the development of character education is also applied to assistance in singing regional songs which aims to shape morals and personality towards God Almighty and towards the community environment.